CRITICAL STUDY OF ESTABLISHMENT OF CHILD SPECIAL CUSTOM CRIMINAL JUSTICE IN THE CHILD CRIMINAL JUSTICE SYSTEM - Adimas Gusti Darmansyah; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
Hugo Grotius is recognized as one of the influential figures in the development of world law, especially in the context of international law so that with his rational and humanist rationale, the criminal justice system in particular has shifted its paradigm to a modern aspect. It is a logical consequence that the progress of juvenile criminal justice also accommodates customary law, especially in West Kalimantan and Indonesia recognizes the existence of customary justice as an effort to handle cases that occur in their environment, as well as cases related to children. In substance, customary law and its legal sanctions still apply to indigenous peoples. These legal values then become an action that is considered good by the community which is then used as a principle in carrying out social activities. These values will then form a norm that guides behavior. legal space to give power to jurors to explore, follow, and understand customary law and use it as a basis for consideration in deciding cases handled. Therefore, it is necessary that a customary court which currently applies strongly to the indigenous Dayak community has a mechanism of customary justice that is able to resolve community problems based on mutual agreement and various existing sanctions indicating that customary justice in society is able to provide a sense of justice.